Case report: Immediate revascularization for symptomatic hepatic artery pseudoaneurysm after orthotopic liver transplantation? A case series and literature review - Lerut, An Verena; Pirenne, Jacques; Sainz-Barriga, Mauricio; Blondeel, Joris; Maleux, Geert; Monbaliu, Diethard (Frontiers in Surgery, 2023)
Introduction. Hepatic artery pseudo aneurysm (HAPA), a rare vascular complication that can develop after liver transplantation, is associated with a high mortality rate and graft loss. To salvage the liver graft, immediate revascularization, either through surgical or endovascular intervention, is required. However currently there is no consensus on the optimal strategy. Here, we report 3 cases of liver transplant recipients diagnosed with HAPA and treated with immediate revascularization. In addition, we present an overview of HAPA cases described in literature and make recommendations how to treat this rare complication. Methods. All adults transplanted in our center between 2005 and 2021 were retrospectively reviewed. Literature search was done in Pubmed for original studies between 1980 and 2021 reporting early hepatic artery (pseudo) aneurysm after liver transplantation requiring either surgical or endovascular intervention. Results. From a total of 1172, 3 liver transplant patients were identified with a symptomatic HAPA and treated with immediate revascularization. HAPA occurred 73, 27 and 8 days post liver transplantation and was treated with immediate revascularization (2 surgical and 1 endovascular intervention). Literature review identified 127 cases of HAPA. In 20 cases, HAPA was managed with endovascular therapy and in 89 cases by surgical intervention. Overall reported mortality rate was 39.6%, whereas overall graft survival was 45.2%. Conclusion. Immediate surgical or radiological interventional excision and prompt revascularization to salvage liver grafts is feasible but still associated with a high mortality.